(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Stunting is a condition of impaired growth in children due to prolonged malnutrition. As a result, children are shorter than normal children of the same age. One of the regions in Indonesia with high stunting rates is Sumedang Regency. Villages included in the stunting locus include Jatihurip Village, Kota Kaler District. The main livelihoods in Jatihurip Village are fisheries, plantations and agriculture. This PKM aims to increase the knowledge of posyandu cadres and UMKM managers by processing PMT food ingredients made from purple sweet potatoes as an effort to reduce stunting, overcome malnutrition problems, families at risk of stunting and improve the economy of UMKMs in Jatihurip Village by providing knowledge about online marketing strategies such as Grabfood, Shopeefood, Gofood, Facebook, etc. The targets of this activity involve cadres and UMKM managers in Jatihurip Village. This PKM activity consists of: (1) counseling about stunting prevention (2) training on making purple sweet potato pudding (3) entrepreneurship training including business based on digitalization/marketing. After providing training, evaluations were carried out to measure the success of the training by distributing questionnaires to posyandu cadres and UMKM managers. Through this approach, it is hoped that most of the cadres and UMKM managers can understand how to make purple pudding and utilize the digitalization system for product marketing provided by the PKM team. The outputs of this PKM are in the form of innovations in making purple sweet potato pudding, increasing competence and skills in posyandu cadres and UMKM managers in utilizing the product marketing system produced independently in an effort to reduce stunting rates and increase the economy in Jatihurip Village.